Biological studies and molecular characterization of a Cryptosporidium isolate from ostriches (Struthio camelus) - Meireles, Marcelo Vasconcelos [UNESP]; Soares, Rodrigo Martins; Bianchi dos Santos, Marcia Merces Aparecida; Gennari, Solange Maria (Amer Soc Parasitologists, 2006)
There are many reports of cryptosporidial infection in ostriches, but none with molecular characterization of the isolates. A study was undertaken for the characterization of a Brazilian Cryptosporidium sp. ostrich isolate by using molecular phylogenetic analysis of fragments of the 18S ribosonial DNA. heat-shock Protein (lisp) 70 coding gene, and actin coding gene. Biological studies were accomplished by the experimental inoculation of chickens via oral or intratracheal routes with fresh ostrich Cryptosporidium sp. oocysts. Molecular analysis of nuceotide sequences of the 3 genes by using neighbor-joining and parsimony methods grouped the ostrich isolate as a sister taxon of Crypiosporidium badeyi and showed that the os(rich isolate is genetically distinct from all other known Cryptosporidium species or genotypes. None of the inoculated chickens developed infection as determined by mucosal smears. histology, and fecal screening for oocysts. Although biological and molecular Studies indicate that the ostrich Cryptosporidium is a new species, further Studies regarding morphological. biological, and molecular characteristics of other ostrich isolates are required to confirm the species status of the ostrich Cryprosporidium.